Philip Roth, The American Trilogy – American Pastoral, I Married a Communist, The Human Stain (ENTHYMEMA, 2011)
Review of Philip Roth. The American Trilogy – American Pastoral, I Married a Comunist, The Human Stain, edited by R. Miller. New York: The Library of America, 2011.